Microwave Perspective on Magnetic Breakout Eruption - Lee, Jeongwoo (Frontiers in Astronomy and Space Sciences, 2022)
Microwave maps may provide critical information on the flux rope interaction and the breakout eruption if their polarization is measured with high precision. We demonstrate this diagnostic capability using the 17 GHz maps from the Nobeyama Radioheliograph (NoRH) of a circular ribbon flare SOL2014-12-17T04:51. The EUV images from SDO/AIA and the coronal magnetic field extrapolated from the HMI magnetogram are also used to support the interpretation of the microwave data. The most direct evidence for the breakout eruption is the sudden change in the sign of the microwave polarization over the AR at heliographic coordinates S20E09, indicating change of the overlying fields from a closed fan structure to a spine-like structure. Another important piece of evidence comes from the spatial and temporal variations of quasi-periodic pulsations (QPP) detected at the 17 GHz. The QPP was more obvious in one loop leg before the eruption and later moved to the spine field region on and after the flare. This indicates that the oscillatory power is transferred from an interacting flux rope to the outer spine, along which the reconnection launches torsional Alfven waves, in good agreement with MHD model predictions for breakout eruption. In the practical viewpoint, these two diagnostics work because microwave observations are free of saturation even in strong flaring regions.